2009
DOI: 10.1152/ajpheart.01276.2008
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Hsp70 on the structure and function of SERCA2a expressed in HEK-293 cells during heat stress

Abstract: Fu MH, Tupling AR. Protective effects of Hsp70 on the structure and function of SERCA2a expressed in HEK-293 cells during heat stress. Am J Physiol Heart Circ Physiol 296: H1175-H1183, 2009. First published February 27, 2009 doi:10.1152/ajpheart.01276.2008.-Heat shock protein 70 (Hsp70) can physically interact with and prevent thermal inactivation of sarco(endo)plasmic reticulum Ca 2ϩ -ATPase (SERCA) 1a, the SERCA isoform expressed in adult fasttwitch skeletal muscle. This study examined whether Hsp70 could p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 59 publications
(79 reference statements)
6
53
1
Order By: Relevance
“…HSP70 exerts a protective effect on the heart (Fu and Tupling, 2009) and brain tissue (Zhao et al, 2006), in addition to playing an important role in immunity. In this regard, HSP70 protects cells from natural killer cells and imparts anti-infective and anti-tumor immunity through its involvement in antigen processing and presentation (Gehrmann et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…HSP70 exerts a protective effect on the heart (Fu and Tupling, 2009) and brain tissue (Zhao et al, 2006), in addition to playing an important role in immunity. In this regard, HSP70 protects cells from natural killer cells and imparts anti-infective and anti-tumor immunity through its involvement in antigen processing and presentation (Gehrmann et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In this case the HSP72 evidently recognized and bound to targets within the fibers because of alterations in target proteins rather than alterations in the HSP72 itself. It is likely that SERCA is the predominant binding site of the HSP72 in the skinned fibers here, given 1) the propensity of SERCA to bind HSP72 (13,14,45), 2) the comparatively high absolute number of SERCA proteins present in muscle fibers [ϳ100 and 20 -35 mol/kg wet weight in EDL and SOL muscle, respectively (34,49)], and 3) the relatively greater additional HSP72 binding occurring in the EDL fibers compared with SOL fibers (Fig. 6) [see also INTRODUCTION and Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, we have recently shown that in rat SOL muscles heated in vitro to 45°C for 30 min, Ͼ95% of the HSP25 and ␣B-crystallin became tightly bound within the fibers and did not diffuse out even when all internal membranes were dispersed with the detergent Triton X-100 (21). HSP72, in contrast, appears to bind in stress situations primarily to membrane proteins, and in particular has been found to bind to and stabilize the structure and function of the sarco(endo)plasmic reticulum Ca 2ϩ -ATPase pump (SERCA1a and SERCA2a) in skeletal and cardiac muscle following heat stress (13,45). In apparent accord, we have recently reported that the absolute amounts of HSP72 in skeletal muscles are much lower than the density of SERCA pumps [HSP72 content ϳ1.1 and 4.6 mol/kg wet weight in rat extensor digitorum longus (EDL) and SOL muscle (21), and total SERCA content ϳ100 and ϳ20 -35 mol/kg, respectively (34, 49)], that heat treatment of skeletal muscles to 45°C causes tight binding of Ͼ95% of the HSP72 present, and that exposure of such heat-treated fibers to Triton X-100 for 10 min caused diffusional loss of a similar proportion (ϳ50% to 70%) of both the HSP72 and the SERCA (21).…”
mentioning
confidence: 99%
“…Frozen tissues were homogenized in a solution containing (in mM) 250 sucrose, 5 HEPES, 10 NaN 3, and 0.2 PMSF, using a Polytron homogenizer. Ca 2ϩ -dependent Ca 2ϩ -ATPase activity in homogenates was measured at 37°C, as described previously (12,13). The data were analyzed by nonlinear regression with computer software (GraphPad Software), and the KCa values were calculated using an equation for a general cooperative model for substrate activation.…”
Section: Slnmentioning
confidence: 99%